2016
DOI: 10.1371/journal.pone.0165830
|View full text |Cite|
|
Sign up to set email alerts
|

Sarcosine Up-Regulates Expression of Genes Involved in Cell Cycle Progression of Metastatic Models of Prostate Cancer

Abstract: The effects of sarcosine on the processes driving prostate cancer (PCa) development remain still unclear. Herein, we show that a supplementation of metastatic PCa cells (androgen independent PC-3 and androgen dependent LNCaP) with sarcosine stimulates cells proliferation in vitro. Similar stimulatory effects were observed also in PCa murine xenografts, in which sarcosine treatment induced a tumor growth and significantly reduced weight of treated mice (p < 0.05). Determination of sarcosine metabolism-related a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 41 publications
(49 reference statements)
3
32
0
Order By: Relevance
“…Sarcosine one‐carbon metabolism is regulated by the androgen receptor (AR), and androgen supplementation results in increased DNA methylation in prostate cancer . Interestingly, sarcosine upregulates AR expression, indicating a reciprocal regulatory relationship . Although sarcosine is mainly known as a prostate cancer‐associated metabolite, it has also been implicated in a subset of metastatic breast cancer cases.…”
Section: Amino Acidsmentioning
confidence: 99%
“…Sarcosine one‐carbon metabolism is regulated by the androgen receptor (AR), and androgen supplementation results in increased DNA methylation in prostate cancer . Interestingly, sarcosine upregulates AR expression, indicating a reciprocal regulatory relationship . Although sarcosine is mainly known as a prostate cancer‐associated metabolite, it has also been implicated in a subset of metastatic breast cancer cases.…”
Section: Amino Acidsmentioning
confidence: 99%
“…Also, the mere addition of sarcosine to cultured benign prostate epithelial cells induced an invasive phenotype (4). Although the sarcosine metabolism is well-characterized, its metabolic functions in the human body are still poorly understood and are currently under active investigation (5,22).…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, the organ distribution of 11 C-sarcosine was determined in 2 male and 2 female Sprague-Dawley rats at 5 time points (5,15,30,60, and 90 min) using injected doses of 7.4-28 MBq of 11 C-sarcosine. Groups of animals were sacrificed while under isoflurane anesthesia.…”
Section: C-sarcosine Biodistributionmentioning
confidence: 99%
See 1 more Smart Citation
“…∼1–3 μM in healthy individuals compared with 9–15 μM in patients with prostate cancer) . There is not a consensus on the possible role of sarcosine, but some studies have suggested that sarcosine accumulates in the tumor and exhibits a stimulatory effect on growth in malignant/metastatic prostate cells due to its conversion to serine and glycine .…”
Section: Introductionmentioning
confidence: 99%